EFFECT OF AMMONIA-ETHANOL MOLE RATIO ON THE SILICA NANOPARTICLES SYNTHESIZED FOR RHODAMINE B DYES ADSORPTION - Yayuk Puji Lestari; Amaria Amaria (Jurnal Kimia Riset, 2023)
Various ammonia-ethanol mole ratios were successfully used for the synthesis of silica nanoparticles for rhodamine B adsorption. This study aims to determine the characteristics of the adsorbent at different ammonia-ethanol mole ratios, maximum adsorption at pH, and contact time. Several steps, including extraction of Na2SiO3 from rice husk ash, synthesis of adsorbents with ammonia-ethanol mole ratios (14:1, 21:1, 28:1, and 42:1), and their characterization. The parameters studied in the adsorbent include the functional groups, particle size, maximum pH, and rate constant adsorption. The FTIR results showed that all adsorbents had functional groups, indicating the presence of silica. The results suggest that the optimum mole ratio of NS 14:1 particles has a size of 39.82 nm. The optimum adsorption of rhodamine B by NS 14:1 occurred at a pH 3 of 0.00419 mmol.g-1 and a contact time of 40 min. The rate constant of adsorption by NS 14:1 was 102.42 g.mmol-1.min-1 followed a pseudo-second order kinetic model.